2004
DOI: 10.4049/jimmunol.173.12.7444
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Type 3 Complement Receptor for TNF-α Suppression, Immune Evasion, and Progressive Pulmonary Fungal Infection

Abstract: TNF-α is crucial in defense against intracellular microbes. Host immune cells use type 3 complement receptors (CR3) to regulate excess TNF-α production during physiological clearance of apoptotic cells. BAD1, a virulence factor of Blastomyces dermatitidis, is displayed on yeast and released during infection. BAD1 binds yeast to macrophages (Mφ) via CR3 and CD14 and suppresses TNF-α, which is required for resistance. We investigated whether blastomyces adhesin 1 (BAD1) exploits host receptors for immune deviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…This is supported by the influences of GA in models of graft-vs-host disease and inflammatory bowel disease (26). In a recently published study, GA was found to shift the cytokine production of monocytes toward a more anti-inflammatory profile in a MBP-independent fashion (47); ␣ M ␤ 2 is highly expressed on monocytes, and we speculate that GA binding to ␣ M ␤ 2 could be a contributing factor consistent with other observations that ligand binding to this receptor may regulate cytokine production (48).…”
Section: Discussionsupporting
confidence: 70%
“…This is supported by the influences of GA in models of graft-vs-host disease and inflammatory bowel disease (26). In a recently published study, GA was found to shift the cytokine production of monocytes toward a more anti-inflammatory profile in a MBP-independent fashion (47); ␣ M ␤ 2 is highly expressed on monocytes, and we speculate that GA binding to ␣ M ␤ 2 could be a contributing factor consistent with other observations that ligand binding to this receptor may regulate cytokine production (48).…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, morphological and physiological plasticity allows fungi to rapidly adapt to changing extracellular conditions. Species-specific signaling and morphological features appear to be a direct result of fungal attempts to survive as new microenvironments, and their particular cell stresses, were encountered (Hogan and Klein 1994;Newman et al 1995;Batanghari et al 1998;Sebghati et al 2000;Gow et al 2002;Brandhorst et al 2004;Rappleye et al 2004Rappleye et al , 2007Gantner et al 2005;Nemecek et al 2006;Gauthier and Klein 2008;Nather and Munro 2008;Mora-Montes et al 2011;. The concerted action of morphotype and physiological changes in the context of a particular environment are therefore critical for successful fungal adaptation (Butler et al 2009;O'Connor et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, binding and phagocytosis via the CD11b/CD18 macrophage does not trigger leukotriene release [44] or a respiratory burst [45,46], suggesting noninflammatory functioning. Furthermore, CD11b/ CD18 was shown to be immunosuppressive by downregulation of IL-12 and IFN-g production [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%